Floating Inductance Simulator with Electronic Tuning Property Using only Active Elements - Roongmuanpha, Natchanai; Mongkolwai, Pratya; Pukkalanun, Tattaya; Dumawipata, Teerasilapa; Tangsrirat, Worapong (My University, 2023)
This paper discusses the active-only electronically tunable floating lossless inductance simulator, which uses a single fully balanced-voltage differencing buffered amplifier (FB-VDBA) and one operational amplifier (OA). For this implementation, only integrated circuit packages with no external passive components are utilized. The synthetic equivalent inductance value is electronically adjustable via the transconductance gain of the FB-VDBA. Non-idealities of the active element have produced their effects. Using PSPICE with TSMC 0.25-mum CMOS parameter and the LM741 type OA, the performance of the proposed circuit and its application as a second-order voltage-mode lowpass filter is demonstrated. The numerical simulations closely matched the theoretical results.
Keywords: active-only; electronically tunable; Fully Balanced-Voltage Differencing Buffered Amplifier (FB-VDBA); inductance simulator; lossless inductor; Operational Amplifier (OA)